Gender Stereotyping in Family: An Institutionalized and Normative Mechanism in Pakhtun Society of Pakistan. (14th July 2015) - Hussain, Muhammad; Naz, Arab; Khan, Waseem; Daraz, Umar; Khan, Qaisar
Gender stereotyping and gender role development is one of the debatable concerns to sociologists especially those who are interested in sociology of gender. This study attempts to investigate the role of family inculcating gender stereotyping in Pakhtun culture and its impact on gender role development conducted in public-sector universities of Malakand Division, Khyber Pakhtunkhwa province of Pakistan. The data were collected through in-depth interview method using interview guide as a tool of data collection. A sample size of 24 respondents consisting male and female students and teachers (8 samples from each university through purposive sampling technique) was selected from three universities in the region, that is, University of Malakand, University of Swat, and Shaheed Benazir Bhutto University Sharingal (main campus). The collected information has been analyzed qualitatively where primary information has been linked with secondary data for further elaboration and attainment of grounded facts. The study reveals that gender stereotyping and gender role formation are sociocultural and relational constructs, which are developed and inculcated in the institutional network, social interaction, and social relationships especially in family. The study indicated that in family sphere, gender stereotyping and gender role formation are the outcome of gender socialization, differential familial environment, and parents' differential role with children. The study recommends that gender-balanced familial environment, adopting the strategy of gender mainstreaming and positive role of media, can overcome gender stereotyping and reduce its impacts on gender and social role formation.